Uso de equipos electrónicos y prevalencia de síndrome visual informático en estudiantes del 3er año de bachillerato del Colegio Babahoyo periodo junio - noviembre año 2022. - Gorotiza Veliz, Gimger Lourdes (2022)
Introduction: Technological advances have allowed the development of new forms of communication and entertainment, currently the use of technology in both equipment and media allows us to hold videoconferences, we use the internet for multiple tasks such as playing, informing and entertaining ourselves. Teenagers are increasingly integrated into social networks, online games, videos, etc. generating a constant use of this type of electronic equipment such as cell phones and computers. Objective: To identify the prevalence and appearance of the visual computer syndrome in students of the 3rd year of high school of the Babahoyo Educational Unit, period june - november, 2022. Results: 47.7% of the students surveyed show symptoms of Computer Visual Syndrome. The main symptoms detected are: burning (78%) itching (86.2%) eye redness (79.8%) pain (78.4%) difficulty in near vision (43.1%) have also developed sensitivity to light (56.9%) and Finally, the headache symptom is present in (47.7%). 56% use the cell phone or other devices more than 5 hours a day, in addition 44% use it from 3 to 5 hours. Conclusions: there is a high prevalence among students, it is necessary to implement a culture of visual care in homes and encourage outdoor activities.